Factors Influencing Purchase Preferences of Store Brands: Examples from Hypermarkets in Malaysia - Ha, Norbani Che; Kadir, Sharifah Latifah Syed Abdul (UI Scholars Hub, 2008)
This study is to investigate factors that describe consumers' perceptions towards store brands, and important factors that influence consumers towards purchasing store brands. The factor, such as, price, product quality, product risk, familiarity, involvement, intrinsic and extrinsic cues, and familiarity are used to gauge the purchase preferences. The study is carried out in Klang Valley involving two most popular hypermarkets in Malaysia that are Tesco and Giant. Out of 444 consumers that were intercepted and asked to participate only 300 accepted to participate and completed the questionnaire, resulting to 68% response rate. Results of the study indicate that factors such as price, familiarity, and involvement are popular in describing customers' perceptions towards store brands however, only price and familiarity are the determinant in their purchasing of store brands.